Stability of emulsions formulated with high concentrations of sodium caseinate and trehalose - Álvarez Cerimedo, María Soledad (2010)
Stability of emulsions formulated with 10wt.% oil (concentrated fish oil, CFO, sunflower oil, SFO, or olive oil, OO), sodium caseinate concentrations varying from 0.5 to 5wt.%, giving oil-to-protein ratios of 20-2, and 0, 20, 30 or 40wt.% aqueous trehalose solution was studied by Turbiscan. Particle size distribution, microstructure, and small angle X-ray scattering (SAXS) patterns were also obtained. The main mechanism of destabilization in a given formulation strongly depended on oil-to-protein ratio. As evidenced by the BS-profile changes with time, emulsions formulated with 0.5 and 1wt.% NaCas destabilized mainly by creaming while for the 2wt.% NaCas concentration, both creaming and flocculation mechanisms, were involved. The main destabilization mechanism for the 3, 4 or 5wt.% NaCas emulsions was flocculation. Stability of emulsions was also affected by the content of trehalose in the aqueous phase. Trehalose diminished the volume-weighted mean diameter (D4,3) and greatly improved stability.